Prospective analysis of video head impulse tests in patients with acute posterior circulation stroke - Ha, Sang Hee; Lee, Dong Kyu; Park, Gayoung; Kim, Bum Joon; Chang, Jun Young; Kang, Dong-Wha; Kwon, Sun; Kim, Jong S.; Park, Hong Ju; LEE, Eun-Jae (Frontiers in Neurology, 2023)
Background Video head impulse tests (vHITs), assessing the vestibulo-ocular reflex (VOR), may be helpful in the differential diagnosis of acute dizziness. We aimed to investigate vHITs in patients with acute posterior circulation stroke (PCS) to examine whether these findings could exhibit significant abnormalities based on lesion locations, and to evaluate diagnostic value of vHIT in differentiating dizziness between PCS and vestibular neuritis (VN). Methods We prospectively recruited consecutive 80 patients with acute PCS and analyzed vHIT findings according to the presence of dorsal brainstem stroke (DBS). We also compared vHIT findings between PCS patients with dizziness and a previously studied VN group (n = 29). Receiver operating characteristic (ROC) analysis was performed to assess the performance of VOR gain and its asymmetry in distinguishing dizziness between PCS and VN. Results Patients with PCS underwent vHIT within a median of 2 days from stroke onset. Mean horizontal VOR gain was 0.97, and there was no significant difference between PCS patients with DBS (n = 15) and without (n = 65). None exhibited pathologic overt corrective saccades. When comparing the PCS group with dizziness (n = 40) to the VN group (n = 29), patients with VN demonstrated significantly lower mean VOR gains in the ipsilesional horizontal canals (1.00 vs. 0.57, p < 0.001). VOR gain and their asymmetry effectively differentiated dizziness in the PCS from VN groups, with an area under the ROC curve of 0.86 (95% CI 0.74–0.98) and 0.91 (95% CI 0.83–0.99, p < 0.001), respectively. Conclusion Significantly abnormal vHIT results were rare in patients with acute PCS, even in the presence of DBS. Moreover, vHIT effectively differentiated dizziness between PCS and VN, highlighting its potential for aiding differential diagnosis of acute dizziness.